Pemberian Asam Valproat pada Induk Tikus Bunting Menghambat Sintesis Insulin pada Sel Otak Anak Tikus - Komariah, Komariah; Kiranadi, Bambang; Winanto, Adi; Manalu, Wasmen; Handharyani, Ekowati (Faculty of Medicine, Universitas Padjadjaran, 2017)
Asam valproat memengaruhi aktivitas histone deacetylase yang berperan dalam ekspresi gen selama organogenesis. Insulin berperan dalam proliferasi dan diferensiasi sel-sel saraf dentate gyrus hipokampus. Penelitian ini bertujuan mempelajari pengaruh pemaparan asam valproat pada induk bunting terhadap ekspresi gen insulin pada dentate gyrus. Penelitian dilakukan di UPHL IPB pada bulan Mei 2015 hingga Desember 2016 dengan 84 ekor anak tikus yang dilahirkan oleh induk tikus kontrol yang diberi asam valproat 250 mg pada umur kebuntingan 10, 13, dan 16 hari digunakan untuk pengamatan kadar glukosa, insulin, DNA, RNA, dan rasio RNA/DNA serta pengamatan mikroskopis otak. Pengamatan dilakukan selang waktu empat minggu, dimulai dari umur 4 sampai 32 minggu. Anak tikus yang dilahirkan oleh induk tikus yang diberi asam valproat selama kebuntingan mempunyai kadar glukosa otak yang lebih tinggi (p<0,01) dan insulin yang lebih rendah (p<0,05). Selama periode pertumbuhan, anak tikus yang dilahirkan oleh induk tikus yang diberi asam valproat mengalami peningkatan kadar glukosa dan penurunan kadar insulin (p<0.05). Pengamatan mikroskopis sel-sel dentate gyrus menunjukkan degenerasi sel dan tidak terlihat reaksi imunoreaktif terhadap insulin, namun terjadi penurunan konsentrasi DNA, RNA, serta rasio RNA/DNA (p<0,05). Pemberian asam valproat pada induk tikus pada umur kebuntingan 10, 13, dan 16 hari memengaruhi organogenesis otak anak tikus sehingga menyebabkan kerusakan sel-sel saraf penghasil insulin otak yang ditunjukkan oleh penurunan sekresi dan kadar insulin. [MKB. 2017;49(3):156–64]Kata kunci: Asam valproat, dentate gyrus, insulin, organogenesis Valproic Acid Administration in Pregnant Rats Inhibits Insulin Synthesis n in Brain Cells of the OffspringsValproic acid affects the activity of histone deacetylase which eventually affects gene expression during organogenesis. Insulin plays a role in regulating the proliferation and differentiation of the dentate gyrus. This experiment was designed to study the effects of valproic acid administration on the expression of insulin gene in the dentate gyrus of pregnant rats. This study was carried out at the Laboratory Animal Management Unit (UPHL) of Bogor Agricultural University from May 2015 to December 2016, with eighty four newborn rats from control rats and VA-administered rats at the age of 10, 13, and 16 days of pregnancy. The measurements were done for glucose, insulin, DNA, and RNA concentrations in dentate gyrus and to observe the microscopic condition of the brain at the ages of 4 to 32 weeks with 4 weeks interval. Rats born form mothers administered by 250 mg valproic acid during pregnancy had higher glucose concentrations (p<0.01) and lower insulin concentrations (p<0.05) in the dentate gyrus. During the post-natal growth phase, rats born from mothers administered with valproic acid had increased glucose concentrations and decreased insulin concentrations (p<0.05). Microscopic observations of the dentate gyrus showed degeneration of nerve cells with no immunoreaction to insulin was seen in dentate gyrus cells. However, the concentrations of DNA, RNA, and the ratio of RNA/DNA in the dentate gyrus cells decreased (p<0.05). The administration of valproic acid to pregnant rats at the age of 10, 13, and 16 days of pregnancy destructs brain organogenesis of the offsprings which eventually disturbs insulin production in the dentate gyrus indicated by decreased insulin secretion and concentrations. [MKB. 2017;49(3):156–64]Key words: Dentate gyrus, insulin, organogenesis, valproic acid